2019
DOI: 10.1016/j.ctro.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of organ motion-based robust optimisation for VMAT planning for breast and internal mammary chain radiotherapy

Abstract: Highlights Evaluation of organ-motion based robust optimisation for breast VMAT. Organ-motion based robust optimisation generates clinically acceptable plans. Technique validated by recalculating robust plans on real patient CBCT data. The technique generated plans that are robust to changes to the patient shape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…The main disadvantage of this method was that dose distribution of radiotherapy plan used for the nal evaluation was not optimized based on actual radiotherapy implementation status, so this plan was not guaranteed to be the actual optimal solution. Moreover, since VB removed away, the nal dose distribution was inadequate for protection of organs at risk compared with the initial optimized results 14 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The main disadvantage of this method was that dose distribution of radiotherapy plan used for the nal evaluation was not optimized based on actual radiotherapy implementation status, so this plan was not guaranteed to be the actual optimal solution. Moreover, since VB removed away, the nal dose distribution was inadequate for protection of organs at risk compared with the initial optimized results 14 .…”
Section: Introductionmentioning
confidence: 98%
“…Fredriksson proposed that adding Robust optimization could signi cantly increase the patient's skin dose, and to some extent, it could replace the e cacy of VB22 . The Alex Dunlop team added Robust optimization to study breast cancer radiotherapy based on organ motion, found that D 98 , D 95 , D 50 and D 2 of CTV that added Robust optimization were signi cantly different from treatments without Robust optimization (P<0.01), they proposed that the use of robust optimization based on organ motion to generate VMAT plan is clinically acceptable for the typical and extreme target area changes during treatment14 . Hideharu Miura et al veri ed the advantages of introducing Robust in other tumor types with greater CTV activity, such as Larynx cancer,Robust-optimized plan had better CTV coverage rate than that without Robust-optimized, and less carotid artery exposure dose…”
mentioning
confidence: 99%
“…Alternatively, future work may further develop sitespecific models of anatomical variation for breast treatments to handle these uncertainties via scenario-based robust optimization methods. For example, Dunlop et al [31] suggested a robust optimization approach for VMAT planning using a PTV margin and a number of simulated CTs representing anatomical changes of the breast with motions of the breast CTV. The primary goal of this work is to evaluate the benefit of combining an FBL and a LINAC in a treatment room for breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Strong robustness was needed in precision radiotherapy, especially like dose painting which put forward non-uniform prescribed dose in CTV to escalate the dose to regions of high risk and meanwhile de-escalate the dose of the low-risk region. Recently, The robustness optimization methods had been developed by incorporating uncertainty in plan optimization, for CTV should receive the prescribed dose depended on desired dose distribution and dose fall-off near the target rather than geometric margin [29]. Lowe, M. et al [30] believed robustness optimization was an effective method to reduce dose to normal tissues that would be unnecessarily irradiated with the PTV-margin concept.…”
Section: Discussionmentioning
confidence: 99%